Diagnosis of Helicobacter pylori infection by invasive and noninvasive tests - Pourakbari, Babak (Brazilian Society of Microbiology, 2013)
Although several invasive and noninvasive tests have been developed for the diagnosis of Helicobacter pylori infection, all of the tests have their limitations. We conducted a study to investigate and compare the suitability of rapid urease test (RUT), serology, histopathology and stool antigen tests with polymerase chain reaction (PCR) for detection of H. pylori, and correlate the diagnostic methods with PCR. Eighty nine patients (61 adults, 28 children) referred to the Firoozgar Hospital and Children Medical Center Hospital for diagnostic upper gastrointestinal endoscopy entered to the study and noninvasive tests such as immunoassay for serological antibodies against H. pylori and detection of its antigen in feces were measured. The biopsies were utilized for histological examination, RUT and PCR. The H. pylori statuses were evaluated by the positivity of ureC PCR in biopsy specimens and 53 subjects had H. pylori positive result. Histopathology showed high overall performance in adults and children with sensitivity and specificity 100% and 90%, respectively. Sensitivity, specificity, and accuracy for stool antigen test were 87.8%, 75% and 82%, respectively. Correlation of RUT, serology (IgG), histopathology and stool antigen tests with PCR were 0.82, 0.32, 0.91 and 0.63, respectively. In conclusion, the RUT and histopathology are as accurate as the PCR of biopsy and stool antigen test can consider as appropriate noninvasive test for detection of H. pylori infection.